THE INFORMATION SYSTEM FOR THE IMPLEMENTATION OF THE HUMAN RESOURCES PROGRAM (HRIS) AT THE OFFSHORE CONSTRUCTION COMPANY PT. GUNANUSA UTAMA FABRICATORS - Suflani, Suflani; Pandjaitan, MM. Lanny W.; Lukas, Lukas (International Journal of Multidisciplinary Research and Literature, 2024)
This research is about Human Resources Information Systems (HRIS) at PT. Gunanusa Utama Fabricators, offshore platform construction company. The research was conducted from January to March 2024, with the number of employees working at this company varying each month: 256 employees in January, 281 employees in February, and 331 employees in March. Descriptive methods with a qualitative approach were used to collect data through in-depth interviews, participant observation and documentation studies. The research results show that HRIS significantly increases the efficiency of HR administration by automating processes, enabling more informed decision making based on data, and optimizing employee skills management. However, the main challenges faced include resistance to change from employees and changes in organizational culture required to support the adoption of new technologies. Large and complex companies, with most employees being contract workers, add to the challenges in implementing HRIS. This research emphasizes the importance of effective change management in overcoming these barriers to maximize the benefits of HRIS in the context of the dynamic construction industry